Chionanthus monteazulensis (Oleaceae), a new species from the campo rupestre of Espinhaço Range, Brazil - Zavatin, Danilo Alvarenga; Almeida, Roberto Baptista Pereira; Ramos, Renato; Lombardi, Julio Antonio [UNESP] (Magnolia Press, 2023)
The new species Chionanthus monteazulensis, from Minas Gerais State, Brazil, is here described and illustrated. It differs from somewhat similar C. fluminensis by the inflorescence size, two stamens (vs. four), the smaller and orbicular or wideelliptic blades, and the smaller petals and fruits.
Keywords: Endemism; Lamiales; Neotropics